2020
DOI: 10.3390/en13205366
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the K-Mg-Ca Sulfate System as Part of Monitoring Problematic Phase Formations in Renewable-Energy Power Plants

Abstract: Besides the widely applied hydropower, wind farms and solar energy, biomass and municipal and industrial waste are increasingly becoming important sources of renewable energy. Nevertheless, fouling, slagging and corrosion associated with the combustion processes of these renewable sources are costly and threaten the long-term operation of power plants. During a high-temperature biomass combustion, alkali metals in the biomass fuel and the ash fusion behavior are the two major contributors to slagging. Ash depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The calculations and assessments were performed using the FactSage 7.1 software package [38]. Details on the optimization method were described in our recent openly accessible article [39].…”
Section: Thermodynamic Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculations and assessments were performed using the FactSage 7.1 software package [38]. Details on the optimization method were described in our recent openly accessible article [39].…”
Section: Thermodynamic Optimizationmentioning
confidence: 99%
“…As the TGA curves in Figure 7 show, mass loss of the sample upon heating and cooling is negligible. Therefore, the overall chemical composition of the analyzed sample was assumed to be constant during the thermal cycles, as indicated in Figure 6, i.e., along the accessible article [39].…”
Section: Dsc Measurement Datamentioning
confidence: 99%
“…The temperature of the melt could be not lower than 1000–1020°C, i.e. not lower than the estimated melting point of K 2 Ca 2 (SO 4 ) 3 (Morey et al , 1964; Tesfaye et al , 2020 and references therein).…”
Section: Discussionmentioning
confidence: 79%
“…The investigations of the deposits showed that sulfur usually occurs in the second deposit layer, and its content reaches a high value, and the quantity of deposits does not decide the rate of corrosion. Moreover, the presence of K2SO4 is an additional factor that could influence the behavior of the eutectics [33]. It is possible to mitigate the corrosion potential of the fuel by applying carefully selected fuel mixtures [36] or fuel valorization techniques.…”
Section: The Problem Of the Fire-side Corrosionmentioning
confidence: 99%